Métodos não farmacológicos para alívio da dor no parto: construção e validação de cartilha educativa - Balsells, Marianne Maia Dutra (2018)
This research aimed to develop an educational primer , aimed at pregnant women in prenatal care, on non-pharmacological methods for pain relief in labor and delivery. It is a methodological study carried out in the period from 2017 to 2018, divided into three stages: 1) Elaboration of the booklet; 2) Validation by the judges and evaluation of the suitability of the material and 3) Validation by the target audience, according to Sabino's study (2016). At the stage of writing the booklet, held consultations in obstetrics books, technical manuals s Ministry of Health, Organization website Non Governmental and scientific articles through integrative review, in order to select the contents related to the theme. The primer was titled "What Do You Know About Non-Pharmacological Methods for Pain Relief in Labor and Delivery? Let's get to know!", Containing non-pharmacological methods for pain relief at birth, as well as information on labor, obstetric violence and pregnancy rights. Hi F applied Readability index Flesch and then made the preparation of the illustrations and layout of the booklet. For the appearance and content validation, they were contacted 24 judges content, 12 Judg zes with teaching experience and 12 judges with health care experience; 3 technical judges with experience in designer , all selected by snowball sampling, following pre-established criteria. For validation by the target group, 30 pregnant women were selected for convenience in a natural childbirth center, located in Fortaleza-CE. The period of data collection with judges and pregnant women occurred between September and November 2018. Three instruments were used for data collection: two for the judges and one for the target audience. For the organization and analysis of the data the Microsoft Excel Program, version 2007 was used. The research was approved by the Research Ethics Committee of the Federal University of Ceará. As for the validation of the first version of the booklet, the content judges attributed a good overall IVC of 0.925 and an excellent concordance level between 97.2 and 98.9%. In the evaluation performed with the Suitability Assesment of Material, the judges rated the booklet as "superior" with an average of 85.2%. The technical judges validated the primer with an overall IVC of 0.97 and agreement level between 83.3 and 100%. In the evaluation carried out with Suitability Assesment of Material , judges classified the booklet as "superior" with an average of 77.5%. The target audience validated the second version of the booklet with an excellent overall IVC of 0.98 and a level of agreement of 99.7% for both clarity and relevance. The final version was completed with 36 pages, based on suggestions made by content judges, technical judges and target audiences. It is concluded that the educational booklet "What do you know about non-pharmacological methods for pain relief in labor and delivery? Let's get to know! ", Was considered valid as to content and appearance to be used with pregnant women, and therefore, be considered a relevant educational technology in the use in prenatal consultation.